The Application of Educational Science from an Islamic and Western Perspective According to Rusydi Ahmad Thu'aimah - Vemby Lamara Verti Madani (Penerbit Hellow Pustaka, 2025)
This paper critically discusses the concept of Total Quality in Education by comparing its origins, connotations, and implications from Western and Islamic perspectives. The author argues that many imported educational concepts, including Total Quality, are adopted without a deep understanding of their original cultural context in the West, which may contradict the contributions of Islamic education and culture. On one hand, the concept of Total Quality in the West is rooted in the administrative revolution (starting from Frederick Taylor up to Deming and Juran) and developed in societies that have undergone political, economic (post-industrial), and social revolutions prioritizing principles such as freedom, equality, customer satisfaction, and continuous improvement. However, the paper highlights that the aim of Western education, even in its most refined form, tends to produce materialistic individuals who are materially rich but spiritually bankrupt. On the other hand, the paper emphasizes the necessity of an Islamic connotation to enrich and strengthen the concept of Total Quality in education. The objectives of Islamic education are directed towards three main pillars: cultivating the earth (material and spiritual development), worship of Allah, and human vicegerency (Khilafah). To achieve comprehensive total quality, Islamic education must be based on twelve core concepts from the Qur'an and Sunnah, including: Ihsan (doing good in the best possible way or excellence), Ishlah (reform or improvement), Itqan (perfection in work), Syura (consultation), Amar Ma'ruf Nahi Munkar (enjoining what is right and forbidding what is wrong), Ikhlas in Work (sincerity), The Concept of Work (the basic axis of human existence), Knowledge (that leads to God), Hikmah (wisdom, knowing the truth and acting upon it)Time (utilizing life in the best way), Uswah (good role model), Ta'awun (cooperation in goodness), Sense of Responsibility. Concludes that the concept of Total Quality sought by Muslims must have a different purpose and meaning than that of the West, which is to produce individuals who integrate science and technology with the warmth of faith and are ready to carry the message of justice, freedom, and humanity.